Analysis on Evaluation Method for Support Equipment System Effectiveness. (November 2020) - Yue, Deng; Chao, Hou
Abstract: In order to study the applicability of evaluation method in the process of service support equipment effectiveness evaluation, this paper selects several kinds of evaluation method which are widely used in the field of equipment effectiveness evaluation, summarizes their basic ideas and general steps, analyzes the application of each evaluation method in the process of service support equipment effectiveness evaluation, and provides a theoretical reference for the practical application of logistics support equipment system effectiveness evaluation method.